PENGARUH LAMA JAM KERJA PADA IBU BEKERJA TERHADAP PEMBERIAN ASI EKSKLUSIF - Sri Wulan Ratna Dewi; Vira Ainun Nisa; Neli Sunarni; Rosidah Solihah (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Exclusive breastfeeding (according to WHO) is breastfeeding only for infants up to 6 months of age without additional fluids or other foods. Exclusive breastfeeding is giving only breast milk without other food and drinks. Exclusive breastfeeding is recommended for the first 6 months of life (WHO, 2005). Background: Breastfeeding in Indonesia has not been fully implemented and there is still very low level of exclusive breastfeeding, especially for working mothers. From the results of observations made by researchers, data was obtained that 8 out of 10 working mothers who breastfeed (babies aged 6-12 months) do not exclusively breastfeed their babies, and 9 out of 10 non-working mothers who breastfeed (babies aged 6-12 months) giving exclusive breastfeeding to the baby. Purpose: To determine the relationship between employment status and exclusive breastfeeding. Methods: This type of research is analytic with a cross sectional approach, with job status as the independent variable and exclusive breastfeeding as the dependent variable, using 21 samples. Result: This research was conducted using quantitative methods, namely by distributing a form in the form of a g-form so that it can be concluded that there is a relationship between long working hours for working mothers and exclusive breastfeeding. Conclusion: there is a relationship between work status and exclusive breastfeeding.